Investigation of prevalence of infestation with head lice and some factors affecting on them in infected people in Kirkuk city, Iraq - Fadhil Mahdi Rasheed; Fatima Shihab Al-Nasiri (Tikrit Journal of Pure Science, 2022)
The current study was made during the period from July to November 2020. The infestation with head lice was searched for residents of Kirkuk city, and a random samples (1988 cases) were collected from city residents and check up their scalps to detect the head lice infestation. This study aims to determinate the prevalence of head lice infestation in  different regions of Kirkuk city and to demonstrate the role of some epidemiological factors on the infestation as age, gender, nature of hair tissue, hair length, hair density. The current study showed the head lice infestation reached 117 cases with a total prevalence of infestation 5.88%. These results come from a clinical study that made on 1988 people from a variety of age groups, society, social-economic and cultural groups. The highest prevalence of infected was recorded (15.11%) for the age group 6-12 years, while the lowest prevalence of infected was for the age group 46-80 years (0.42%). The present research concluded that the infestation was higher in female than male (9.35, 2.10%, respectively). The highest prevalence of infected was in straight hair (3.40 and 11.76%) for both male and female (respectively), and the lowest prevalence of infestation was for curly hair (2.30%) in female, while the infestation for curly hair in male are not recorded. The results also showed the highest prevalence of infestation was in long hair (10.79 and 12.16%) than in short hair (0.63 and 3.63%) for both male and female (respectively). The highest prevalence of infestation was also recorded for high dense hair (3.13 and 12.63%) compared with low dense hair (0.66 and 1.65%) for both male and female (respectively).